The Terminal Velocity of Compound Drops in Flotation Units - Morales, Rigoberto (2020)
The behavior of the terminal velocity of gas-liquid compound drops was studied experimentally. The eect of the size of the internal bubble was analyzed, covering a wide range of relative sizes. The bubble signicantly increased the buoyancy eects, particularly for denser external uids. The terminal velocity increases with the size of the internal bubble, suggesting that the motion is governed by the geometry of the compound drop. A mechanistic model was proposed, and it showed a good agreement with the measurements.